FORMATION OF A STRATEGY FOR ADAPTIVE AND INNOVATIVE DEVELOPMENT OF ENTERPRISES IN THE CONDITIONS OF DIGITALIZATION - OBYDIENNOVA, Tetiana; CHOBITOK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In modern conditions of digital transformation of the economy, enterprises are faced with the need to radically update strategic approaches to their own development. The rapid development of digital technologies creates new requirements for flexibility, innovation and adaptability of business. Traditional management models are increasingly inconsistent with the dynamics of the modern market, which requires the implementation of adaptive and innovative strategies as a guarantee of survival and growth of enterprises in the digital era. The lack of a single methodology for forming such strategies, as well as the limited experience of domestic enterprises in this area, determine the scientific novelty and applied significance of the topic. In modern conditions of economic transformation, accompanied by active digitalization of the business environment, there is a growing need to form new approaches to strategic management of enterprise development. Digital technologies not only change the nature of economic activity, but also radically transform management paradigms, requiring enterprises to be flexible, innovative and able to adapt quickly. In this context, the concept of adaptive and innovative development as a strategic vector for ensuring competitiveness, sustainability and dynamic growth of enterprises is of particular relevance. In the process of the study, it was substantiated that the strategy for adaptive and innovative development of an enterprise in the context of digital transformation should be based on the principles of dynamic flexibility, openness to innovation, proactive change management and integration of digital technologies into all functional areas of activity. It was determined that the formation of such a strategy requires the use of a systemic approach, which includes: analysis of the level of digital maturity of the enterprise; diagnostics of internal resources and innovative potential; identification of external threats and opportunities in the digital environment; development of strategic scenarios taking into account digital trends. Particular attention is paid to the use of modern digital tools in strategic planning, which allows for more accurate forecasting, timely adaptation to changes and personalization of management decisions. The results of the study confirm that digitalization is a key factor in the transformation of strategic management of enterprises, causing the need to transition to adaptive and innovative development models. This approach involves the implementation of flexible, systemic and technologically sound strategies that ensure increased innovative activity, digital maturity and competitiveness of the enterprise. The use of digital tools in strategic management allows to significantly improve the processes of analytics, forecasting, making management decisions and responding promptly to changes in the external environment. The practical implementation of the proposed approaches will contribute to the formation of sustainable competitive advantages, effective adaptation to the challenges of the digital economy and long-term growth of enterprises.